2015
DOI: 10.3854/crm.5.085.carolina.v1.2015
|View full text |Cite
|
Sign up to set email alerts
|

Terrapene carolina (Linnaeus 1758) – Eastern Box Turtle, Common Box Turtle.

Abstract: The Eastern Box Turtle, Terrapene carolina (Family Emydidae), as currently understood, contains six living subspecies of small turtles (carapace lengths to ca. 115-235 mm) able to close their hinged plastrons into a tightly closed box. Although the nominate subspecies is among the most widely distributed and well-known of the world's turtles, the two Mexican subspecies are poorly known. This primarily terrestrial, though occasionally semi-terrestrial, species ranges throughout the eastern and southern United S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 86 publications
2
29
4
Order By: Relevance
“…Eastern box turtles inhabit temperate and subtropical regions over much of the eastern United States [16]. The species is of conservation concern because populations have declined from habitat loss, road mortality, intense predation (particularly of nests and juveniles), and collection for the pet trade [22]. As such, the species is listed as Vulnerable by the IUCN and is included in CITES Appendix II [23].…”
Section: Study Species and Animal Husbandrymentioning
confidence: 99%
“…Eastern box turtles inhabit temperate and subtropical regions over much of the eastern United States [16]. The species is of conservation concern because populations have declined from habitat loss, road mortality, intense predation (particularly of nests and juveniles), and collection for the pet trade [22]. As such, the species is listed as Vulnerable by the IUCN and is included in CITES Appendix II [23].…”
Section: Study Species and Animal Husbandrymentioning
confidence: 99%
“…The Eastern Box Turtle (Terrapene carolina) is a nominally terrestrial turtle found in temperate forests and early successional mosaics throughout the eastern United States (Dodd 2001, Keister andWilley 2015), including Longleaf Pine forests of the southeast region (Greenspan et al 2015). However, relatively little is known of their ecology in fire-prone systems of any kind (but see Platt et al 2010, Howey and Roosenburg 2013, Roe et al 2017, with only limited information on survivorship, growth rates, body condition, and other vital rates with population-level consequences.…”
Section: Introductionmentioning
confidence: 99%
“…We also examine individual variation in responses to spatial and temporal heterogeneity of fire at the fire-maintained site. Terrapene carolina is a species of conservation concern that is in decline in many parts of its broad geographic range (Keister and Willey 2015), and it may serve valuable functional roles in areas where it is still common (Liu et al, 2004;Dodd 2006;Jones et al 2007;Lovich et al 2018). It is thus important to understand responses of T. carolina to fire and other forest management practices and apply this knowledge to inform conservation and management strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this species is more susceptible to road mortality than other turtle species because they tend to close their shell when threatened and remain closed for longer periods of time [90]. Increased road traffic will increase the probability of mortality and assuming no further habitat changes, will lead to a threshold effect that causes widespread local extinction [91]. Although we found that there will be more suitable habitat in the future, it may not do any good with continued habitat fragmentation.…”
Section: Discussionmentioning
confidence: 82%